Sección especializada para casos de beligerancia política y cancelaciones de credenciales (S.E.T.S.E) - Aguirre Caballero, William H. (2018)
The Supreme Electoral Court of Costa Rica undertook the ambitious task of creating the Specialized Section, as part of its internal organization, for first instance resolution of any complaints for cancellation or annulment of credentials of municipal officials appointed through popular election and any complaints for political bias or belligerence, the incorporation of the electoral review appeal as a procedural instrument to review the actions taken at first instance. The article analyzes the legal grounds for the creation of said specialized section.